A Comparative Analysis of the Impact of Translation Techniques on the Translation of Similes and Metaphors in The Old Man and The Sea - Pratiwi, Aulia Rachma; Yannuar, Nurenzia; Subiyanto, Arif (Journal of Language and Literature, 2023)
Figurative language is a way to captivate readers, expressed through writing in a more creative style. This research aims to find out and compare the translation techniques used by Sapardi Djoko Damono and Dian Vita Ellyati to translate similes and metaphors in The Old Man and The Sea Novel and their effect on the quality of the translation. This research used a descriptive qualitative method that employed a sampling technique. The research data are similes and metaphors from The Old Man and the Sea and its two Indonesian translations. This research collects data from document analysis, questionnaires, and focus group discussions. This research shows that translation techniques used in similes and metaphors have different impacts on the translation quality in both versions. The final result of the calculation shows that version A has a final translation quality score of 2.42, while version B has a final quality score of 2.54. The findings highlight the importance of carefully considering and selecting appropriate techniques to convey figurative language in translated works effectively. Future research in this field could focus on exploring additional translation strategies for other forms of figurative language, investigating the preferences, and examining the influence of cultural context on the translation process.